The Financial Sustainability of Small and Medium-Scale Pharmacy Businesses in Naga City - Panga, Daniel Lorenzo; Galvez, Shirley (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study determined the financial sustainability of small and medium-scale pharmacy businesses in Naga City, Camarines Sur, Philippines, during Fiscal Year 2025. Specifically, it examined the business profile of pharmacies, the extent of financial sustainability practices in terms of investment and planning, understanding customer needs, cost optimization, managing revenue and expenses, and inventory management, as well as the challenges affecting sustainability. The study employed a descriptive-evaluative-inferential research design involving 197 respondents composed of pharmacy owners, managers, pharmacists, cashiers, and accounting staff from small and medium-scale pharmacy businesses. Data were collected using a validated survey questionnaire and analyzed through frequency count, percentage, weighted mean, rank order, and the Wilcoxon Mann-Whitney U-Test. Findings revealed that most pharmacies operated as sole proprietorships, had been in operation for 1–10 years, employed 1–9 personnel, and generated average monthly incomes ranging from ₱100,001 to ₱500,000. Financial sustainability practices were generally much evident across all dimensions, including investment and planning, understanding customer needs, cost optimization, managing revenue and expenses, and inventory management, with cost optimization, receiving the highest rating. The study also found that pharmacies experienced challenges related to rising drug costs, supply chain disruptions, staffing shortages, increasing operational expenses, and compliance with regulatory requirements. Significant differences were observed in the rank orders of financial sustainability practices and challenges between small and medium-scale pharmacies, indicating that business scale influences sustainability capacity and responses to operational pressures. The study concludes that strengthening financial planning, operational efficiency, inventory control, and regulatory compliance is essential for enhancing long-term sustainability among community pharmacies. The study supports Sustainable Development Goal (SDG) 3 on Good Health and Well-Being and SDG 8 on Decent Work and Economic Growth by promoting sustainable pharmaceutical services and strengthening local enterprises. Its sustainability contribution lies in supporting public health access, economic resilience, and the long-term viability of community pharmacy businesses.